PERAN IKLIM ORGANISASI MEMODERASI PENGARUH KOMPETENSI DAN MOTIVASI GURU TERHADAP KINERJA GURU (Studi Pada Guru PNS di SMK Negeri Kab. Pati) (Students' Journal of Economic and Management, 2013)
This study aims to analyze The Influence of Competence and Motivation to the Teachers Performance with the Organisational Climate as moderate variable at SMK negeri in Pati Regency. This study belongs to the type of quantitative research using a survey method of descriptive analysis approach. Population of this study are 134 teacher, while the samples taken as many as 100 teacher as respondent and using a Slovin method and purposive sampling. Measurements using a Likert scale with 5 (five) alternative answer. Test instruments used are the validity and reliability. While the test model used is the coefficient of determination and F test (Goodness of Fit). Hypothesis testing used in this study used regression analysis. The results of the first model showed the coefficient of determination (Adjusted R Square) is 0,566, the meaning of the result is that the Competence and Motivation together have a 56,6% impact to the Techers Performance and the rest are influenced by others variables. Based on the research result can be summarized as follows: (i) Competence is positive and significant effect to the Teachers Performance, (ii) ) Motivation is positive and not significant effect to the Teachers Performance, (iii) the Organisational Climate is positive and significant effect to the Teachers Performance (iv) Organisational Climate is not moderating to the effect of Competence to Teacher Performance, (v) Organisational Climate is not moderating to the effect of Motivation to Teacher Performance Keywords :      Competence, motivation, Organisational Climate, Teachers Performance